The Impact of Scientific Vocational Training for Career Choice - Deepak Chakravarty, Dr. Mahima Gupta (International Journal of Modern Agriculture, 2021)
Objectives: This study will focus on gauging the impact of scientific vocational training on career choices. Methods: Without proper vocational training, students are not able to get proper jobs, not satisfied whether at the personal life. Previous literature reviews, journals, books, etc., have been considered for the study. Findings: Vocational Education programs for youth will make them a better individual to know and accept their personality and interest, as they select a vocation of their choice where they can develop a self-reliant life in future without seeking for a white-collar job or be floating in the labor market. Novelty: Novelty in the training themes and methods helps in engaging students initially. It helps in encouraging them to apply and practice their freshly learned knowledge in new circumstances and situations. This is very important for consolidating their understanding, memory, and transfer of knowledge.